Análisis de la demanda de un destino Pet Friendly en la ciudad de Guayaquil - Arriaga Quizhpi, Daniela Casandra (2021)
Guayaquil has pet friendly establishment, they are places which allow people to go into them with pets and offer different services such as food, lodging, spa, walks, among others. This type of establishment is very important because it allows tourists to be accompanied by their best friend, be it canine, feline or birds because they are another member of the family, with whom to share new experiences. The present investigation objective is to analyze the demand for the pet friendly destination Guayaquil city, where we define it as a product that people are willing to buy depending on the different factors and one of them is the economic part, but through the surveys that were carried out. From the surveys carried out it was known that the current demand is low because tourists are unaware of the pet-friendly services in the Guayaquil. Through descriptive research, it was possible to identify the main characteristics of the object of study, where convenience sampling was used to determine the size of the population to be surveyed in the city. Finally, with the results of the interview and the surveys carried out, it was possible to observe that the problem for the low pet friendly demand is because some owner of touristic places and the tourist market have not adopted them yet completely. According to the information collected, is made know some services are announced offered within pet friendly establishments in the Guayaquil city to tourists with pets.